Peran Saksi dalam Persidangan sebagai Pendorong Keadilan: Studi Kasus Pencurian Sepeda Motor - Sembiring, Gelora Rehliasta; Rumapea, Lidia; Simanjuntak, Agatha Sofia; Ayu, Fanny Mustika; Manurung, Yunita Tri Carnova; Siahaan, Parlaungan Gabriel; Batu, Dewi Pika Lumban (CV. Rayyan Dwi Bharata, 2024)
This research examines the role of witnesses in motorbike theft cases which ended in peaceful resolution through a restorative justice approach. The main focus lies on how witnesses can influence the trial and mediation process in an effort to achieve balanced justice between the perpetrator and the victim. The method used is a normative juridical approach, which refers to legal studies and related documents to understand the role of witnesses as evidence and promoters of justice. The research results show that witness testimony plays an important role in revealing facts, supporting the mediation process, and preventing decision-making errors in court. Witnesses also function as moral monitors who ensure that restorative justice is carried out transparently and protects the rights of victims. This research suggests the need for systematic integration of restorative justice in the legal system, better witness protection, and public education regarding the importance of the role of witnesses in the judicial process.